Analisis Kapasitas Peralatan Pembangkit Listrik Tenaga Surya Rooftop dengan Simulasi Pvsyst - JAELANI, FAHRUL; SYAHRIAL (e-Proceeding FTI, 2024)
The PLTS system is one of the new renewable energies that has the potential to be developed in Indonesia. The configuration used is On-Grid and PVsyst software which is located in the Mechanical Engineering Building at SMKN (X). This study aims to determine the optimal PLTS design, analyze equipment capacity, analyze annual electricity costs and analyze carbon emission reduction. The results of this study, from a rooftop area of 400 m², will produce a power of 81 kWp using 450 Wp solar panel equipment, 180 units, String Combiner Box using the 4 input 2 output model, Grid solar inverter used Huawei Inverter with 2 MPPT, capacity 40 kW , Combiner Box capacity 1 x 30 kW . With a capacity of 81 kWp, there will be savings in paying electricity bills, originally an average bill of Rp. 22,546,496 per month to Rp. 17,878,421 per month with a large savings of Rp. 4,668,075 Contribution to reduce Indonesia’s carbon emissions in the building by 21% or by 54.607,28 Kg of Co2/ year. Keywords: Configurations, Pvsyst Applications, PLTS Equipment, Savings on Electricity Payments, Carbon Emissions Sistem PLTS merupakan salah satu energi baru terbarukan yang berpotensi untuk dikembangkan di Indonesia. Konfigurasi yang digunakan On-Grid dan software PVsyst yang berlokasi di Gedung Teknik Mesin SMKN (X). Penelitian ini bertujuan untuk mengetahui Desain PLTS yang optimal, analisis kapasitas peralatan, analisis biaya listrik tahunan dan analisis penurunan emisi karbon. Hasil penelitian ini , dari luas rooftop bangunan 400 m² akan menghasilkan daya sebesar 81 kWp menggunakan peralatan solar panel 450 Wp, 180 unit, string Combiner Box menggunakan model 4 input 2 output, Grid solar inverter yang digunakan Inverter Huawei dengan 2 MPPT, kapasitas 40 kW, Combiner Box kapasitas 1 x 30 kW . Dengan kapasitas 81 kWp maka akan terjadi penghematan pembayaran rekening listrik semula rata-rata tagihan Rp 22.546.496 per bulan menjadi sebesar Rp 17.878.421 per bulan dengan besar penghematan Rp 4.668.075 Kontribusi menurunkan emisi karbon Indonesia pada gedung tsb 21 % atau sebesar 54.607,28 Kg Co2/ tahun. Kata Kunci: Konfigurasi, Aplikasi Pvsyst, Peralatan PLTS, Penghematan Pembayaran Listrik, Emisi Karbon